2020
DOI: 10.1371/journal.pone.0237262
|View full text |Cite
|
Sign up to set email alerts
|

Raw milk and fecal microbiota of commercial Alpine dairy cows varies with herd, fat content and diet

Abstract: The factors that influence the diversity and composition of raw milk and fecal microbiota in healthy commercial dairy herds are not fully understood, partially because the majority of metataxonomic studies involve experimental farms and/or single factors. We analyzed the raw milk and fecal microbiota of 100 healthy cows from 10 commercial alpine farms from the Province of Trento, Italy, using metataxonomics and applied statistical modelling to investigate which extrinsic and intrinsic parameters (e.g. herd, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 95 publications
1
9
0
1
Order By: Relevance
“…Milk fat is the main nutrient component of milk and has become one of the important traits in dairy cow breeding . In recent years, increasing evidence has shown that microRNAs play important roles in the synthesis of milk fat in the bovine mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Milk fat is the main nutrient component of milk and has become one of the important traits in dairy cow breeding . In recent years, increasing evidence has shown that microRNAs play important roles in the synthesis of milk fat in the bovine mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes, Bacteroidetes, and Verrucomicrobia were also the dominant phyla in yak, and the Firmicute:Bacteroidetes ratio was significantly decreasing from winter grassland to feedlot feeding [ 7 ]. In dairy cattle, diet was the most important parameter to explain fecal microbiota richness, and fecal microbiota of mixed (forage and concentrate) diet was more richness than that of dry forage diet [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Geçmiş 5000 yıla bakıldığı zaman, birçok insan popülasyonu diyetlerinde geviş getiren hayvanların (inek, keçi, koyun ve manda) sütünü sağlıklı beslenmenin bir parçası olarak kullanmışlardır. 2 Bu hayvanlardan elde edilen sütün (özellikle çiğ süt) sağlıklı beslenmede bu kadar çok tercih edilmesi, kendine özgü endojen mikrobiyal topluluğa sahip olduğu bilgisinden gelmektedir. Özellikle yeni doğan bebeklerde anne sütü, bebeğin sağlıklı bir yaşam sürdürmesi adına yararlı olan birçok biyoaktif moleküller sağladığından, doğumdan sonraki ilk dönemlerinde büyüme ve gelişme için ideal beslenme şeklidir.…”
Section: Introductionunclassified